1961
DOI: 10.1042/bj0780051
|View full text |Cite
|
Sign up to set email alerts
|

The amide nitrogen content of gelatins

Abstract: PHOSPHOLIPIDS IN OX LIVER 51 rancid phosphatides, whose amount is small in relation to the total phospholipid. 3. Degraded phosphatides were present in the fraction expected to contain phosphatidic acid. It was therefore considered impossible either to exclude or confirm the presence of naturally occurring phosphatidic acid. 4. The bearing of these facts on the isolation of phosphatidic acid reported by Hubscher & Clark (1960) is discussed. 5. Linoleic acid (70 %) and linolenic acid (12-15 %) were the main fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1962
1962
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…36 The active role of the collagen fibrils probably resides in the specific aggregation of the collagen molecules and the particular stereochemical and electrochemical array of their side chains. 35 It was demonstrated that solution pH can affect the electrochemical property of collagen, such as the dissociation of the acidic and basic groups of collagen molecules 37,38 and ion-binding characteristics of collagen fibrils. 39 The isoelectric point of tropocollagen of calf skin 37 is reported to be pH 8.3 and that of pig skin gelatin 38 is approximately pH 9.4.…”
Section: Discussionmentioning
confidence: 99%
“…36 The active role of the collagen fibrils probably resides in the specific aggregation of the collagen molecules and the particular stereochemical and electrochemical array of their side chains. 35 It was demonstrated that solution pH can affect the electrochemical property of collagen, such as the dissociation of the acidic and basic groups of collagen molecules 37,38 and ion-binding characteristics of collagen fibrils. 39 The isoelectric point of tropocollagen of calf skin 37 is reported to be pH 8.3 and that of pig skin gelatin 38 is approximately pH 9.4.…”
Section: Discussionmentioning
confidence: 99%
“…The isoelectric point of gelatin can vary between 9.4 (no modification of amide groups) and 4.8 (90-95% of free carboxylic acid groups) (Eastoe et al, 1961). Acid-processed gelatins have high isoelectric points because the less severe processing conditions maintain the value near to that of collagen.…”
Section: Isoelectric Pointmentioning
confidence: 99%
“…This is confirmed by the results of Table 1. The lowering of the isoionic point of a protein as the side-chain amide groups are converted to free carboxyl groups has been observed for gelatin (Eastoe et al, 1961). Removal of all the amide groups by alkali treatment caused the isoionic point of gelatin to fall from above 9 to 4.8.…”
Section: Discussionmentioning
confidence: 96%